Spectrum of Breast Diseases in a Breast Clinic of a Tertiary Care Hospital - Sara Malik , Usman Qureshi, Jahangir Sarwar Khan, Salman Shafique, Sarosh Afzal Farooqi, Gohar Rasheed, Syed Waqas Hassan, Hamza Waqar Bhatti, Sara Malik , Usman Qureshi, Jahangir Sarwar Khan, Salman Shafique, Sarosh Afzal Farooqi, Gohar Rasheed, Syed Waqas Hassan, Hamza Waqar Bhatti (Journal of Rawalpindi Medical College, 2019)
Background: To determine the pattern and clinical presentation of breast diseases in different age groups presenting to a breast clinic. Methods: It was a retrospective descriptive study which included all patients presenting to a breast clinic for three years. Age at presentation, symptoms, clinical features, investigations, operative findings and specimen reports were recorded and submitted for analysis. . Results: A total of 3568 patients were included. Mastalgia was the commonest findings (39.42%) followed by fibroadenoma(15.83%) and carcinoma of breast (12.61%). Pain in the breast was the commonest presenting symptom (40.38%). Lump in the breast was found in 22.84%, while pain and lump were present in 27.27% of patients. Among carcinoma breast, intra ductal carcinoma was the commonest (57.55%) followed by malignant phyllodes tumour (17.77%). Conclusion: Most common breast diseases presenting in our setting are mastalgia, fibroadenoma and breast carcinoma. Dedicated breast clinic in our public sector hospitals is need of time. It will help to create awareness about breast diseases among general public and will be a source to collect data about disease burden so that future policies can be streamlined